2016
DOI: 10.3329/bjms.v15i1.20497
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of anxiety psychopathology experienced among postgraduate medical trainees

Abstract: Objectives: Postgraduate medical training is characteristically intensive and stressful. Given that anxiety disorders are often linked with stress-related scenarios; awareness of the burden of anxiety disorders among postgraduate medical trainees and their determinants is essential for informed intervention. This study was set to investigate the pattern of anxiety psychopathology, and to determine its correlates among doctors in a Nigerian postgraduate medical training facility.Methods: The participants, made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
1
0
2
Order By: Relevance
“…Reino Unido de ansiedad generalizada entre el 4,9% (Olagunju et al, 2016) y el 12% (Earle et al, 2005), del 3,4% para el trastorno obsesivo compulsivo (TOC) (Olagunju et al, 2016), del 2,4% para fobias simples (Olagunju et al, 2016), del 2% para el trastorno de pánico (Earle et al, 2005) y del 1,5% para fobia social (Olagunju et al, 2016). Curiosamente, un autor establece una prevalencia de 30,5% de fobia social según el cuestionario SPIN (Social Phobia Inventory) (Melo et al, 2016).…”
Section: Lydall Et Al 2009unclassified
See 1 more Smart Citation
“…Reino Unido de ansiedad generalizada entre el 4,9% (Olagunju et al, 2016) y el 12% (Earle et al, 2005), del 3,4% para el trastorno obsesivo compulsivo (TOC) (Olagunju et al, 2016), del 2,4% para fobias simples (Olagunju et al, 2016), del 2% para el trastorno de pánico (Earle et al, 2005) y del 1,5% para fobia social (Olagunju et al, 2016). Curiosamente, un autor establece una prevalencia de 30,5% de fobia social según el cuestionario SPIN (Social Phobia Inventory) (Melo et al, 2016).…”
Section: Lydall Et Al 2009unclassified
“…Entre los factores asociados al consumo de alcohol destacan: género masculino, residentes de especialidades quirúrgicas, extraversión, deprivación de sueño, mayor número de guardias, síntomas depresivos, síntomas ansiosos, ideación suicida activa, intentos de suicidio previos, consumo de drogas ilícitas y mayor estrés percibido (Bunch et al, 1992;Lebensohn et al, 2013;Mansukhani et al, 2012;Martinez, et al, 2016;Olagunju et al, 2016;Pereira-Lima et al, 2016).…”
Section: Lydall Et Al 2009unclassified
“…Some studies have reported a higher prevalence of psychopathology among doctors compared to the general population (Melo-Carrillo, Van Oudenhove, & Lopez-Avila, 2012;Romo-Nava et al, 2019;Schwenk, Davis, & Wimsatt, 2010;Dyrbye, Thomas, & Shanafelt, 2006;Quince, Wood, Parker, & Benson, 2012), where depression, anxiety (Olagunju, Ogundipe, Lasebikan, Coker, & Asoegwu, 2016), substance use (Cottler et al, 2013), and suicidal risk prevail (Dutheil et al, 2019). As a consequence, poor academic performance, attrition, deterioration in patient care, and suicide are documented (Coentre & Figueira, 2015;Coentre, Faravelli, & Figueira, 2016;Dyrbye et al, 2006;Quince et al, 2012).…”
Section: Introductionmentioning
confidence: 99%